Networked learning in higher education: practitioners' perspectives - Chris Jones; Mirea Asensio; Peter Goodyear (Association for Learning Technology, 2000)
This paper arises from the work of the JISC Committee on Awareness, Liaison and Training (CALT)-funded 'Networked Learning in Higher Education' project. Networked learning is a term that has had a currency for some years now and can be seen as part of the development of a new paradigm in education (Harasim, Hiltz, Teles and Turoff, 1995; Koschmann 1996; Romiszowski and Ravitz, 1997). We have defined networked learning as learning in which C&.IT is used to promote connections: between one learner and other learners; between learners and tutors; between a learning community and its learning resources.